THE EARLY OLIGOCENE FLORA OF SANTA GIUSTINA (LIGURIA, ITALY) - REVISION AND COMPARISON WITH THE FLORA OF THE TARD CLAY FORMATION (Rivista italiana di Paleontologia e Stratigrafia, 2010)
Based on palaeobotanical material preserved at the University of Genoa, Italy (DIP.TE.RIS.), a revision of the Early Oligocene flora of Santa Giustina, as well as the 1916 monograph of Principi, was undertaken. It is shown that apart from members of the Lauraceae family, Eotrigonobalanus furcinervis and Sloanea olmediaefolia were dominant in the flora, which was mainly composed of warmth-demanding species. The site is primarily characterized by remnants of the vegetation developed under warm and moist climate and abundant water supply. A few additional plants from the neighboring zonal vegetation are also present. The flora is quite reminiscent of that of the Tard Clay Formation, part of the Inner Carpathian Region, providing a proven link to the floristic relationships of these areas. Up to the Pre-Neogene, the Inner Carpathian Region and the surrounding Alpine-Carpathian-Dinaric Region was composed of a composite terrane that 1) existed independently from Stable Europe, and, 2) had a much more southerly position than today. This terrane collage was sharply bordered from all directions except west, as is supported by new evidences of the floristic affinities with the Santa Giustina flora.